Memorialisation Principles, Post-Civil War Reintegration and the Quest for Sustainable Peace in Nigeria - Philip Ademola Olayoku (IFRA-Nigeria, 2017)
Mnemonic devices have remained integral to human learning processes through history, as man continues to grapple with his existential experiences. Such epistemological consideration considers knowledge as a universal experience of recall, whereby events, objects, texts and processes are commited to memory. However, threats to Nigeria's sociopolitical life has been the reverse of this logic with the erasure of History from the curriculum of secondary schools until the recent attempts at its restoration. It is such neglect that prompted this study's examination of the need to revive the consciousness of the importance of historical lessons in the consolidation of the country's democracy by adopting a memorialisation policy. It conceptualizes memorialisation within the framework of creation of public memorials as important for national integration and peacebuilding through references to extant memory initiatives. It then proceeds to situate the eight principles of memorialisation - as proposed by Impunity Watch - within the global context while drawing from an array of literature within the humanities and social sciences. In relaying this to the Nigerian context, the paper focuses on relevant historical events and discussions around the Nigerian Civil War with the purpose of demonstrating how memorialisation can be adopted in facilitating peacebuilding efforts in Nigeria, as a means to address different secessionist bids in a sustainable manner.